Survey data of intra-household decision making and smallholder agricultural production in northern Uganda and southern Tanzania - Mwungu, Chris Miyinzi; Mwongera, Caroline; Shikuku, Kelvin Mashisia; Nyakundi, Fridah Nyabate; Twyman, Jennifer; Winowiecki, Leigh Ann; Ampaire, Edidah L.; Acosta, Mariola; Läderach, Peter R.D. (Elsevier, 2017)
This article provides a description of intra-household survey data that were collected in Uganda and Tanzania in 2014 and 2015, respectively. The surveys were implemented using a structured questionnaire administered among 585 households in Uganda and 608 in Tanzania. Information on decision making processes in agricultural production was collected from the principal adult male and female decision-makers in each household. The survey consisted of two parts. Firstly, the decision-makers, both male and female of each household were jointly interviewed. Secondly, individual interviews were carried out, questioning the decision-makers separately. The datasets include both household and individual level data containing numeric, categorical and string variables. The datasets have been shared publicly on the Harvard dataverse.